2000
DOI: 10.1002/1097-4687(200008)245:2<87::aid-jmor1>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the nervous system of Myzostoma cirriferum (Annelida) as revealed by immunohistochemistry and cLSM analyses

Abstract: The nervous systems of juvenile and adult Myzostoma cirriferum Leuckart, 1836, were stained with antisera against 5-HT (5-hydroxytryptamine, serotonin), FMRFamide, and acetylated ␣-tubulin in combination with the indirect fluorescence technique and analyzed by confocal laser scanning microscopy. The central nervous system consists of two small cerebral ganglia, connected by a dorsal commissure, a ventral nerve mass, and a pair of long circumesophageal connectives joining the former to the latter. The two neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 5 publications
2
41
0
Order By: Relevance
“…In conclusion, myzostomes are platyzoans that exhibit a complicated mixture of annelid-like (Rouse andFauchald 1997a, b, Müller andWestheide 2000), basal spiralian (Haszprunar 1996b, Zrzavý et al 1998), and platyzoan/prosomastigozoan (Mattei and Marchand 1987, 1988, Eeckhaut et al 2000, Zrzavý et al 2001 characters, as well as unique features possibly linked with their parasitic lifestyle. These results suggest that major body-plan characters (segmentation, parapodia) might have been independently lost or gained in different animal phyla (see Eeckhaut et al 2000).…”
Section: Myzostomidamentioning
confidence: 96%
See 2 more Smart Citations
“…In conclusion, myzostomes are platyzoans that exhibit a complicated mixture of annelid-like (Rouse andFauchald 1997a, b, Müller andWestheide 2000), basal spiralian (Haszprunar 1996b, Zrzavý et al 1998), and platyzoan/prosomastigozoan (Mattei and Marchand 1987, 1988, Eeckhaut et al 2000, Zrzavý et al 2001 characters, as well as unique features possibly linked with their parasitic lifestyle. These results suggest that major body-plan characters (segmentation, parapodia) might have been independently lost or gained in different animal phyla (see Eeckhaut et al 2000).…”
Section: Myzostomidamentioning
confidence: 96%
“…The characters supporting annelid origin of the myzostomes (Nielsen 1995, Rouse and Fauchald 19951997a, b, Rouse 1999, Müller and Westheide 2000 are usually either symplesiomorphic (e.g., spiral cleavage, trochophora-like larva, multiciliary epithelial cells) or convergent (e.g., annelid-like chaetae are present in most annelids, myzostomes, echiurids, and some brachiopods, in the ectoproct gizzard armature, and in the cephalopod Kölliker organs; see Lüter andBartolomaeus 1997, Lüter 2000). Myzostomes possess metameric paired organs like protonephridia and parapodia (five pairs), but numbers of so-called "lateral organs" (of uncertain homology), of marginal cirri, and of gut diverticles do not accord with the protonephridial and parapodial numbers.…”
Section: Myzostomidamentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical methods and confocal laserscanning microscopy were used to study the development of the nervous system in B. viridis (Hessling 2001(Hessling , 2002Hessling and Westheide 2002). This combination of methods has proven to be very informative in the study of neurogenesis and in many cases has revealed previously unreported details in neuronal structures of various invertebrate taxa (see, for example, Harzsch et al 1997;Müller and Westheide 2000). The present study is the first application of these techniques in a species of Echiura with planktotrophic larval development.…”
Section: Introductionmentioning
confidence: 97%
“…immunoreactivity is known to be widespread in protostome stomatogastric NS, e.g. in Gnathostomulida (Müller and Sterrer 2004), Annelida (Müller and Westheide 2000; and catenulid and rhabditophoran flatworms (Reuter and Halton 2001;Reuter et al 2001a;Kotikova et al 2002), and it is present also in post-metamorphic cnidarians (Grimmelikhuijzen 1983a(Grimmelikhuijzen , 1938b. Both 5-HT-and FMRFamide immunoreactivity was detected in the gut of tornaria larvae of enteropneusts (Nezlin and Yushin 2004), while it is absent in cnidarian, polyclad and lophotrochozoan larvae (Ruppert 1978;Hay-Schmidt 1995;Dickinson et al 1999;Hessling 2002;Voronezhskaya et al 2002;Wanninger and Haszprunar 2003).…”
Section: Discussionmentioning
confidence: 99%